High-valued utilization method of polyurethane foam degradation solid product
By crushing, crushing, mixing and surface modification of waste polyurethane foam, dispersions that can be used for sponge preparation are prepared, solving the problem that solid products cannot be used at a high value, and improving resource utilization and industrial degradation efficiency.
Patent Information
- Application Number
- CN202411183357.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-27
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2044-08-27
AI Technical Summary
The solid products produced by the degradation of the waste polyurethane soft foam are difficult to utilize at a high value and cannot be well dispersed in the composite polyol, resulting in a low resource utilization rate.
After crushing and crushing, mixing with composite polyether polyol, adding epoxy-based surface modifier, ball milling and sanding treatment, a dispersion with particle size of 20-100 microns is prepared for the preparation of sponge reinforcement agent. , the role of substituting polymer polyols.
It realizes the effective recycling and reuse of waste polyurethane foam solid products, improves resource utilization, solves the problem that solid products cannot be used at a high value, and provides a more efficient and lower cost industrial degradation path.
Smart Images

Figure CN119241797A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for resource utilization of bulk waste polymer materials, in particular to a method for high-value utilization of solid products obtained by chemical degradation of waste polyurethane soft foam. Background Art
[0002] Polyurethane soft foam (commonly known as sponge) is widely used in home furnishing, transportation and other fields due to its excellent resilience and fatigue resistance. With economic development and people's growing demand, the use of polyurethane soft foam is increasing day by day, and the amount of waste is also increasing. However, because its waste cannot be naturally degraded, it can only be disposed of by incineration or landfill, which poses a huge challenge to the environment. In this context, developing degradation technology for waste polyurethane and realizing high-value utilization of recycled products throughout their life cycle has become a research hotspot.
[0003] At present, the degradation methods of waste polyurethane include alcoholysis, acidolysis, etc., the essence of which is that small molecule diols or organic acids depolymerize polyurethane and convert it into smaller molecular weight chemicals such as polyols, thereby realizing the degradation and recycling of resources. However, both acidolysis and alcoholysis methods are prone to produce solid components incompatible with polyols, which come from the non-degradable polyurethane hard segment (polyurea generated by the reaction of isocyanate and water). The solid product is usually difficult to further reuse at a high value. Studies have shown that although there are reports that a large amount of solid products will exist after polyurethane degradation, effective utilization methods are often not proposed. For example, Chemical Engineering Journal 395(2020)125102 only introduces the structural formula of the solid product, but does not discuss its reuse.
[0004] Generally, after polyurethane degradation, its urea-containing fragments that are not completely depolymerized are dispersed in the polyol in a solid state and used directly. However, if the polyols in the recovered components are fully separated, the actual value of the depolymerization product will be greatly improved. The applicant successfully achieved the phase separation of polyols and urea-containing fragments by utilizing the innovation of degradation methods and catalysts, greatly improving the reuse value of recovered polyols, but there is still the problem that the solid products need to be further processed and reused. Therefore, it is necessary to develop a high-value utilization method for solid products produced by polyurethane degradation. Chinese invention patent CN113717434B discloses a method for degrading polyurethane soft foam using acidic ionic liquids. The recovered polyether polyol containing solid products obtained by degradation by this method can be used in the production of regenerated polyurethane soft foam, further improving the commercial value of polyurethane foam degradation. However, the invention does not describe in detail the treatment method of solid products in the degradation products. Chinese invention patent CN114106281A discloses a modification method for recovering and regenerating polyols and its recycling in the polyurethane industry. The method realizes the recycling of polyurethane foam materials through alcoholysis technology. Although this technology realizes the recycling of polyurethane foam, it also does not provide a detailed description of the treatment method of the solid products in the degradation products. Summary of the invention
[0005] In order to overcome the problem that the solid products (PUSR) generated after the degradation of waste polyurethane cannot be reused and the solid products cannot be well dispersed in PPG to achieve high-value utilization, the present invention provides a method for high-value utilization of solid products of polyurethane foam degradation. The method can effectively process PUSR into a sponge reinforcing agent to replace the role of polymer polyol (POP, commonly known as white oil), and at the same time has good dispersibility and compatibility, and can be used to prepare polyurethane foam to achieve full utilization of polyurethane degradation products.
[0006] The technical solution of the present invention is as follows:
[0007] A method for high-value utilization of a polyurethane foam degradation solid product comprises the following steps:
[0008] Step 1: crushing and grinding the solid product produced after degradation to obtain a powdery solid;
[0009] Step 2: Mix the powdered solid and the composite polyether polyol in a mass ratio of 20-50:80-50, and add the mixed mixture into a ball mill;
[0010] Step 3: Adding epoxy surface modifier to the ball mill;
[0011] Step 4: placing the ball milling jar in a ball mill for ball milling to obtain a dispersion;
[0012] Step 5: Place the dispersion obtained in step 4 in a sand mill, use zirconium oxide balls as sand milling media, add triethylamine, and perform sand milling to obtain a dispersion with a particle size of 20-100 microns. Prepare a sponge using the dispersion with a particle size of 20-100 microns.
[0013] Further preferably, a method for high-value utilization of a polyurethane foam degradation solid product comprises the following steps:
[0014] Step 1: The solid PUSR produced after degradation is separated from the polyol and then mechanically crushed and pulverized at high speed to obtain a powdery solid with a particle size controlled at 10-1000 mesh.
[0015] Step 2: Mix powdered PUSR with two or more composite polyether polyols with a molecular weight of 500-3000 g / mol and a hydroxyl value of 50-100 mgKOH / g in a mass ratio of 20-50:80-50, add the mixture into a ball mill, and place ball mill beads of appropriate proportion in the ball mill.
[0016] Step 3: Add epoxy surface modifiers such as 1,2-epoxyhexane, ethylene oxide-PEG-ethylene oxide (Mw=1000-10000Da, CAS: 72207-80-8), 1,2-epoxyoctane, 1,2-epoxyheptane, 1,2-epoxydecane, glycidyl phenyl ether, glycidyl methyl ether, 1,2-epoxy-5-hexene, propylene oxide, glycidyl ether, trimethylolpropane triglycidyl ether and allyl alcohol glycidyl ether, etc., to the ball mill. The modifier is one or more of them, and the mass ratio of the surface modifier to PUSR is 0.01-0.1:1.
[0017] Step 4: Place the ball mill in a ball mill and mill at a speed of 100-800 rpm / min for 8-24 hours to obtain a dispersion with a particle size of 50-1000 microns.
[0018] Step 5: At room temperature, the dispersion obtained in step 4 is placed in a sand mill and sanded using 1.5 mm diameter zirconium oxide balls as sand milling media. The sand milling time is 1-3 hours, during which 0.01-1 ml of triethylamine is added, and the sand milling speed is 2000-6000 rpm (the most preferred sand milling speed is 3000 rpm). After sand milling, a dispersion with a particle size of 20-100 μm is obtained for the preparation of sponges.
[0019] This treatment process not only achieves the effective recovery and reuse of solid products in waste polyurethane soft foam, but also improves the application value of the solid product PUSR through a combination of physical and chemical treatment methods, which helps to improve the overall resource utilization rate of polyurethane waste.
[0020] The ball milling treatment time is 8 to 24 hours, and the best time is 12 hours.
[0021] The sizes of the ball mill beads are 3mm, 5mm, and 10mm, and the ratio is 3:2:1.
[0022] The composite polyether polyol is a mixture of a polyol containing double bonds and a polyether polyol, and the mass ratio thereof is 30-50:70-50.
[0023] The polyol containing double bonds is allyl alcohol random polyether methyl end-capped (CAS: 52232-27-6), polyether F-6, and the like.
[0024] The polyether polyol generally has a hydroxyl value of 50-100 mgKOH / g and a molecular weight of 500-4000 g / mol, and preferably has a hydroxyl value of 56 mgKOH / g and a molecular weight of 3500.
[0025] The polyether polyol can be any one of polypropylene glycol PPG2000, polyether polyol 5623, polyether polyol 5602, etc.
[0026] Most preferably, the composite polyether polyol is a mixture of allyl alcohol random polyether methyl terminated purchased from Zhejiang Huangma Technology Co., Ltd. and polyether polyol PPG5623 purchased from Zhejiang Hengfeng New Materials Co., Ltd. in a mass ratio of 3:7.
[0027] The ball mill and the tank body are both made of zirconium oxide.
[0028] In the present invention, the obtained product can be directly used for the foaming of polyurethane foam (using the polyurethane foam preparation method known in the art), replacing the role played by POP, and the addition ratio can be as high as 30wt%, solving the problem that the solid product cannot be used in a high-value manner. In addition, the present invention conducts in-depth research on the recycling and reuse technology route of waste polyurethane foam, optimizes the utilization rate of the degradation product of the chemical degradation method, so that the commercial properties of the obtained polyurethane foam meet market demand.
[0029] Compared with the prior art, the present invention has the following advantages:
[0030] The present invention deepens the technical route of high-value utilization of solid products from the degradation of waste polyurethane foam, further solves the problem that solid products cannot be highly valued and are wasted, and provides a more efficient and lower-cost approach for large-scale industrial degradation of polyurethane foam.
[0031] The composite polyol of the present invention is easy to prepare, easy to operate, low in cost, and convenient for industrial mass use.
[0032] The method of the present invention utilizes physical crushing and chemical surface modification methods to improve the compatibility and dispersibility of the solid product of waste polyurethane foam degradation in the composite polyol. First, ball milling technology is used to further crush the broken waste polyurethane foam and break it into smaller particles to increase its surface area and improve surface activity, providing favorable conditions for subsequent chemical treatment. Then, by adding an epoxy surface modifier that can react with the -COOH or -OH group on the surface of the solid product, in the ball milling environment, the epoxy group is selectively opened and reacts with the carboxyl / hydroxyl group on the solid product, so that the particle surface is grafted with a polar segment with good compatibility with the polyol, thereby improving the dispersibility and stability of the particles in the polyol. At the same time, the addition of triethylamine during the sand milling process helps the system to reach an alkaline environment, which is conducive to the reaction of the hydroxyl group on the particle surface with the double bond in the double-bond polyol, so that the particle surface is grafted with a long chain of polyol, further improving the dispersibility of the solid product in the polyol. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 Schematic diagram of the recovery process in Example 1.
[0034] Figure 2 The chemical structure formula of the acid hydrolysis solid product obtained in Preparation Example 1.
[0035] Figure 3 The chemical structure formula of the alcoholysis solid product obtained in Preparation Example 2.
[0036] Figure 4 Diagram of the reaction process of the functional groups of the acid hydrolysis solid product PUSR with surfactants and polyols containing double bond components.
[0037] Figure 5 Diagram of the reaction process of alcoholysis solid product and polyol containing double bond components.
[0038] Figure 6 Figure 1 shows the recycled polyurethane sponge prepared in Example 1.
[0039] Figure 7 Figure 2 shows the recycled polyurethane sponge prepared in Example 2.
[0040] Figure 8 Figure 3 shows the recycled polyurethane sponge prepared in Example 3.
[0041] Fig. 9 Figure 4 shows the regenerated polyurethane sponge prepared in Example 4.
[0042] Fig.10 Figure 2 shows the recycled polyurethane sponge prepared in Comparative Example 2.
[0043] Fig.11 Figure 3 shows the recycled polyurethane sponge prepared in comparative example 3.
[0044] Fig.12 Figure 4 shows the recycled polyurethane sponge prepared in comparative example 4.
[0045] Fig.13 Figure 5 shows the recycled polyurethane sponge prepared in Comparative Example 5.
[0046] Fig.14 Figure 9 shows the recycled polyurethane sponge prepared in Comparative Example 9. DETAILED DESCRIPTION
[0047] It should be understood that the embodiments of the present invention shown in the exemplary embodiments are only illustrative. Although only a few embodiments are described in detail in the present invention, it is easy for those skilled in the art to appreciate that multiple modifications are feasible without actually departing from the teachings of the subject matter of the present invention. Accordingly, all such modifications should be included within the scope of the present invention. Without departing from the gist of the present invention, other replacements, modifications, changes and deletions may be made to the design, operating conditions and parameters of the following embodiments.
[0048] The present invention is further described in conjunction with specific implementation modes, but the protection scope of the present invention is not limited thereto:
[0049] Unless otherwise specified in the present invention, the raw materials and equipment used can be purchased from the market or are commonly used in the art. The methods in the embodiments, unless otherwise specified, are all conventional methods in the art.
[0050] Preparation Example 1 (acid hydrolysis method)
[0051] A method for preparing a polyurethane foam acid hydrolysis solid product comprises the following steps:
[0052] Take 500g of succinic acid, 1000g of PPG (polyether polyol PPG5623, purchased from Zhejiang Hengfeng New Materials Co., Ltd.), and 20g of zinc acetate and add them to a 20L glass reactor equipped with a pressure reducing device, a heating device, a condensing reflux device and a mechanical stirring device. Set the temperature to 200°C and the stirring speed to 60r / min. After the temperature is heated to 200°C, 2000g of waste polyether polyurethane foam fragments with a diameter of 2-3cm are added to the reactor at a feeding rate of 40g / min. After the polyurethane foam fragments are fed, the speed is adjusted to 150r / min. After the continuous pressure reduction reaction for 4h, the reaction can be stopped and the product can be discharged. The discharged product is treated by centrifugal separation to separate the solid and liquid components. The solid product PUSR is then obtained. The structure diagram of the solid product is shown in Figure 2 shown.
[0053] Preparation Example 2 (alcoholysis method)
[0054] A method for preparing a polyurethane foam acid hydrolysis solid product comprises the following steps:
[0055] 1) Weigh 300 g of ethylene glycol and 1000 g of PPG (polyether polyol PPG5623, purchased from Zhejiang Hengfeng New Materials Co., Ltd.) and add them into a 20 L glass reactor equipped with a pressure reducing device, a heating device, a condensing reflux device and a mechanical stirring device.
[0056] 2) Reaction step: Heat the reactor to 160°C, set the stirring speed to 60r / min, and add 3000g of waste polyether PUF fragments with a diameter of 2-3cm into the reactor at a feeding rate of about 40g / min. After the PUF is added, adjust the speed to 150r / min. After continuous decompression reaction for 5h, the reaction can be stopped and the product can be discharged. The discharged product is processed by centrifugation to separate the solid and liquid components. Then the solid product PUSR is obtained. The structure of the solid product is shown in the figure Figure 3 shown.
[0057] Example 1
[0058] Step 1: The solid PUSR produced after degradation in Preparation Example 1 is mechanically crushed and pulverized at high speed to obtain a powdery solid with a particle size controlled at 10 meshes.
[0059] Step 2: Mix 2kg of powdered PUSR solid with 8kg of composite polyol (allyl alcohol random polyether methyl end-capped purchased from Zhejiang Royal Madrid Technology Co., Ltd. and polyether polyol PPG5623 purchased from Zhejiang Hengfeng New Materials Co., Ltd. in a mass ratio of 3:7). The mixed materials are added to a ball mill. Ball mill beads of different sizes are added to the ball mill, with diameters of 3 mm, 5 mm and 10 mm, respectively, and the number ratio of these beads is 3:2:1.
[0060] Step 3: Add 200 g of ethylene oxide-PEG-ethylene oxide (Beijing Bailingwei Technology Co., Ltd., product number: 1685134, molecular weight average MW1,000) into the ball mill, and the mass ratio of ethylene oxide-PEG-ethylene oxide to PUSR is 0.1:1.
[0061] Step 4: Place the ball mill in a ball mill and mill at 400 rpm / min for 12 hours to obtain a dispersion with a particle size of 80 μm.
[0062] Step 5: At room temperature of 25°C, the dispersion obtained in step 4 was placed in a sand mill and sanded using 1.5 mm diameter zirconium oxide balls as sand milling media. The sand milling time was 2 hours, during which 1 ml of triethylamine was added, and the sand milling speed was 3000 rpm. After sand milling, a dispersion with a particle size of 20-100 μm was obtained for the preparation of sponges. The dispersion viscosity data is shown in Table 1. The regenerated soft polyurethane foam is as follows Figure 6Its mechanical properties are shown in Table 2.
[0063] Example 2
[0064] Step 1: The solid PUSR produced after degradation in Preparation Example 1 is mechanically crushed and pulverized at high speed to obtain a powdery solid with a particle size controlled at 10 meshes.
[0065] Step 2: Mix 2kg of powdered PUSR solid with 8kg of composite polyol (allyl alcohol random polyether methyl end-capped purchased from Zhejiang Royal Madrid Technology Co., Ltd. and polyether polyol PPG5623 purchased from Zhejiang Hengfeng New Materials Co., Ltd. in a mass ratio of 3:7). The mixed materials are added to a ball mill. Ball mill beads of different sizes are added to the ball mill, with diameters of 3 mm, 5 mm and 10 mm, respectively, and the number ratio of these beads is 3:2:1.
[0066] Step 3: Add 200 g of propylene oxide into the ball mill, with the mass ratio of propylene oxide to PUSR being 0.1:1.
[0067] Step 4: Place the ball mill in a ball mill and mill at 400 rpm / min for 12 hours to obtain a dispersion with a particle size of 80 μm.
[0068] Step 5: At room temperature of 25°C, the dispersion obtained in step 4 was placed in a sand mill and sanded using 1.5 mm diameter zirconium oxide balls as sand milling media. The sand milling time was 2 hours, during which 1 ml of triethylamine was added, and the sand milling speed was 3000 rpm. After sand milling, a dispersion with a particle size of 20-100 μm was obtained for the preparation of sponges. The dispersion viscosity data is shown in Table 1. The regenerated soft polyurethane foam is as follows Figure 7 Its mechanical properties are shown in Table 2.
[0069] Example 3
[0070] Step 1: The solid PUSR produced after degradation in Preparation Example 1 is mechanically crushed and pulverized at high speed to obtain a powdery solid with a particle size controlled at 10 meshes.
[0071] Step 2: Mix 2kg of powdered PUSR solid with 8kg of composite polyol (allyl alcohol random polyether methyl end-capped purchased from Zhejiang Royal Madrid Technology Co., Ltd. and polyether polyol PPG5623 purchased from Zhejiang Hengfeng New Materials Co., Ltd. in a mass ratio of 3:7). The mixed materials are added to a ball mill. Ball mill beads of different sizes are added to the ball mill, with diameters of 3 mm, 5 mm and 10 mm, respectively, and the number ratio of these beads is 3:2:1.
[0072] Step 3: Add 200 g of 1,2-epoxydecane into the ball mill, with the mass ratio of 1,2-epoxydecane to PUSR being 0.1:1.
[0073] Step 4: Place the ball mill in a ball mill and mill at 400 rpm / min for 12 hours to obtain a dispersion with a particle size of 80 μm.
[0074] Step 5: At room temperature of 25°C, the dispersion obtained in step 4 was placed in a sand mill and sanded using 1.5 mm diameter zirconium oxide balls as sand milling media. The sand milling time was 3 hours, during which 1 ml of triethylamine was added, and the sand milling speed was 3000 rpm. After sand milling, a dispersion with a particle size of 20-100 μm was obtained for the preparation of sponges. The dispersion viscosity data is shown in Table 1. The regenerated soft polyurethane foam is as follows Figure 8 Its mechanical properties are shown in Table 2.
[0075] Example 4
[0076] Step 1: The solid PUSR produced after degradation in Preparation Example 2 is mechanically crushed and pulverized at high speed to obtain a powdery solid with a particle size controlled at 10 meshes.
[0077] Step 2: Mix 2kg of powdered PUSR solid with 8kg of composite polyol (allyl alcohol random polyether methyl end-capped purchased from Zhejiang Royal Madrid Technology Co., Ltd. and polyether polyol PPG5623 purchased from Zhejiang Hengfeng New Materials Co., Ltd. in a mass ratio of 3:7). The mixed materials are added to a ball mill. Ball mill beads of different sizes are added to the ball mill, with diameters of 3 mm, 5 mm and 10 mm, respectively, and the number ratio of these beads is 3:2:1.
[0078] Step 3: Add 200 g of 1,2-epoxydecane into the ball mill, with the mass ratio of 1,2-epoxydecane to PUSR being 0.1:1.
[0079] Step 4: Place the ball mill in a ball mill and mill at 400 rpm / min for 12 hours to obtain a dispersion with a particle size of 80 μm.
[0080] Step 5: At room temperature of 25°C, the dispersion obtained in step 4 was placed in a sand mill and sanded using 1.5 mm diameter zirconium oxide balls as sand milling media. The sand milling time was 3 hours, during which 1 ml of triethylamine was added, and the sand milling speed was 3000 rpm. After sand milling, a dispersion with a particle size of 20-100 μm was obtained for the preparation of sponges. The dispersion viscosity data is shown in Table 1. The regenerated soft polyurethane foam is as follows Fig. 9 Its mechanical properties are shown in Table 2.
[0081] Application Examples
[0082] Take 30g dispersion, 70g PPG (polyether polyol PPG5623, purchased from Zhejiang Hengfeng New Materials Co., Ltd.), 3.2g H2O, 0.8g silicone oil, 0.05g triethylamine, 0.2g diethanolamine and 0.14g stannous octoate and place them in a plastic beaker, use a high-speed stirring plate to stir at a speed of 2000rpm for 60s until a uniform dispersion is formed; take 46g TDI (toluene diisocyanate, purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.) and add it to the dispersion, continue to use a high-speed stirring plate to stir at a speed of 2000rpm for 10s, and then quickly pour the mixed solution into the mold for molding. After the foaming height no longer changes, move it into a 70℃ oven and keep it warm for 7h before taking it out to obtain a sponge product.
[0083] Comparative Example 1
[0084] Step 1: The solid PUSR produced after degradation in Preparation Example 1 is mechanically crushed and pulverized at high speed to obtain a powdery solid with a particle size controlled at 10 meshes.
[0085] Step 2: Mix 3kg of powdered PUSR solid with 7kg of composite polyol (allyl alcohol random polyether methyl end-capped purchased from Zhejiang Royal Madrid Technology Co., Ltd. and polyether polyol PPG5623 purchased from Zhejiang Hengfeng New Materials Co., Ltd. in a mass ratio of 3:7). The mixed materials are added to a ball mill. Ball mill beads of different sizes are added to the ball mill, with diameters of 3 mm, 5 mm and 10 mm, respectively, and the number ratio of these beads is 3:2:1.
[0086] Step 3: Place the ball mill in a ball mill and mill at 400 rpm / min for 12 hours to obtain a dispersion with a particle size of 80 microns.
[0087] Step 4: At room temperature of 25°C, place the dispersion obtained in step 4 in a sand mill and use 1.5 mm diameter zirconium oxide balls as sand milling media for sand milling. The sand milling time is 2 hours and the sand milling speed is 3000 rpm. After sand milling, a dispersion with a particle size of 20-100 microns is obtained for the preparation of sponge. The viscosity data of the dispersion are shown in Table 1, and the mechanical properties of the regenerated soft polyurethane foam are shown in Table 2. Compared with Examples 1, 2, and 3, the viscosity can be significantly reduced and the mechanical properties of the regenerated soft polyurethane foam are significantly improved through the modification method of the present invention.
[0088] Comparative Example 2
[0089] Step 1: The solid PUSR produced after degradation in Preparation Example 1 is mechanically crushed and pulverized at high speed to obtain a powdery solid with a particle size controlled at 10 meshes.
[0090] Step 2: Mix 3kg of powdered PUSR solid with 7kg of composite polyol (allyl alcohol random polyether methyl end-capped purchased from Zhejiang Royal Madrid Technology Co., Ltd. and polyether polyol PPG5623 purchased from Zhejiang Hengfeng New Materials Co., Ltd. in a mass ratio of 3:7). The mixed materials are added to a ball mill. Ball mill beads of different sizes are added to the ball mill, with diameters of 3 mm, 5 mm and 10 mm, respectively, and the number ratio of these beads is 3:2:1.
[0091] Step 3: Add 300 g of ethylene oxide-PEG-ethylene oxide (Beijing Bailingwei Technology Co., Ltd., product number: 1685134, molecular weight average MW1,000) into the ball mill, and the mass ratio of ethylene oxide-PEG-ethylene oxide to PUSR is 0.1:1.
[0092] Step 4: Place the ball mill in a ball mill and mill at 400 rpm / min for 12 hours to obtain a dispersion with a particle size of 80 μm.
[0093] Step 5: Place the dispersion obtained in step 4 in a sand mill at room temperature of 25°C and use 1.5 mm diameter zirconium oxide balls as sand milling media for sand milling. The sand milling time is 2 hours, during which 1 ml of triethylamine is added, and the sand milling speed is 3000 rpm. After sand milling, a dispersion with a particle size of 20-100 μm is obtained for the preparation of sponges. Recycled soft polyurethane foam such as Fig.10 As shown, its mechanical properties are shown in Table 2. Compared with Example 1, through the modification method of the present invention, when the PUSR mass ratio increases, the viscosity is 1290 mPa·s, which is only slightly higher than that of Example 1, and significantly lower than the viscosity of 7820 mPa·s in Comparative Example 1, and the viscosity can be significantly reduced. At the same time, the 40% indentation hardness and 75% permanent compression deformation rate of the mechanical properties of the recycled soft polyurethane foam prepared by the dispersion have a small increase in the numerical value compared with Example 1, and still meet the requirements of the mechanical properties of commercial foams.
[0094] Comparative Example 3
[0095] Step 1: The solid PUSR produced after degradation in Preparation Example 1 is mechanically crushed and pulverized at high speed to obtain a powdery solid with a particle size controlled at 10 meshes.
[0096] Step 2: Mix 3kg of powdered PUSR solid with 7kg of composite polyol (allyl alcohol random polyether methyl end-capped purchased from Zhejiang Royal Madrid Technology Co., Ltd. and polyether polyol PPG5623 purchased from Zhejiang Hengfeng New Materials Co., Ltd. in a mass ratio of 3:7). The mixed materials are added to a ball mill. Ball mill beads of different sizes are added to the ball mill, with diameters of 3 mm, 5 mm and 10 mm, respectively, and the number ratio of these beads is 3:2:1.
[0097] Step 3: Add 300 g of propylene oxide into the ball mill, with the mass ratio of propylene oxide to PUSR being 0.1:1.
[0098] Step 4: Place the ball mill in a ball mill and mill at 400 rpm / min for 12 hours to obtain a dispersion with a particle size of 80 μm.
[0099] Step 5: At room temperature of 25°C, the dispersion obtained in step 4 was placed in a sand mill and sanded using 1.5 mm diameter zirconium oxide balls as sand milling media. The sand milling time was 2 hours, during which 1 ml of triethylamine was added, and the sand milling speed was 3000 rpm. After sand milling, a dispersion with a particle size of 20-100 μm was obtained for the preparation of sponges. The dispersion viscosity data is shown in Table 1. The regenerated soft polyurethane foam is as follows Fig.11 The mechanical properties are shown in Table 2. Compared with Example 2, when the PUSR mass ratio is increased, the viscosity data is still maintained at 1320 mPa·s, which is only slightly higher than 1010 mPa·s in Example 2, and maintains good viscosity performance. At the same time, the rebound rate of the recycled soft polyurethane foam prepared by the dispersion is 39.2%, the 40% indentation hardness is 144N, and the 75% permanent compression deformation rate is 2.31%. Compared with Example 2, the numerical changes are not large, and still meet the requirements of commercial foam mechanical properties.
[0100] Comparative Example 4
[0101] Step 1: The solid PUSR produced after degradation in Preparation Example 1 is mechanically crushed and pulverized at high speed to obtain a powdery solid with a particle size controlled at 10 meshes.
[0102] Step 2: Mix 3kg of powdered PUSR solid with 7kg of composite polyol (allyl alcohol random polyether methyl end-capped purchased from Zhejiang Royal Madrid Technology Co., Ltd. and polyether polyol PPG5623 purchased from Zhejiang Hengfeng New Materials Co., Ltd. in a mass ratio of 3:7). The mixed materials are added to a ball mill. Ball mill beads of different sizes are added to the ball mill, with diameters of 3 mm, 5 mm and 10 mm, respectively, and the number ratio of these beads is 3:2:1.
[0103] Step 3: Add 300 g of 1,2-epoxydecane into the ball mill, with the mass ratio of 1,2-epoxydecane to PUSR being 0.1:1.
[0104] Step 4: Place the ball mill in a ball mill and mill at 400 rpm / min for 12 hours to obtain a dispersion with a particle size of 80 μm.
[0105] Step 5: At room temperature of 25°C, the dispersion obtained in step 4 was placed in a sand mill and sanded using 1.5 mm diameter zirconium oxide balls as sand milling media. The sand milling time was 3 hours, during which 1 ml of triethylamine was added, and the sand milling speed was 3000 rpm. After sand milling, a dispersion with a particle size of 20-100 μm was obtained for the preparation of sponges. The dispersion viscosity data is shown in Table 1. The regenerated soft polyurethane foam is as follows Fig.12 The mechanical properties are shown in Table 2. Compared with Example 3, when the PUSR mass ratio is increased, the viscosity data is still maintained at 1320 mPa·s, which is only slightly higher than 1010 mPa·s in Example 2, and maintains good viscosity performance. At the same time, the rebound rate of the recycled soft polyurethane foam prepared by the dispersion is 39.2%, the 40% indentation hardness is 144N, and the 75% permanent compression deformation rate is 2.31%. Compared with Example 2, the numerical changes are not large, and still meet the requirements of commercial foam mechanical properties.
[0106] Comparative Example 5
[0107] Step 1: The solid PUSR produced after degradation in Preparation Example 1 is mechanically crushed and pulverized at high speed to obtain a powdery solid with a particle size controlled at 10 meshes.
[0108] Step 2: Mix 2kg of powdered PUSR solid with 8kg of composite polyol (allyl alcohol random polyether methyl end-capped purchased from Zhejiang Royal Madrid Technology Co., Ltd. and polyether polyol PPG5623 purchased from Zhejiang Hengfeng New Materials Co., Ltd. in a mass ratio of 3:7). The mixed materials are added to a ball mill. Ball mill beads of different sizes are added to the ball mill, with diameters of 3 mm, 5 mm and 10 mm, respectively, and the number ratio of these beads is 3:2:1.
[0109] Step 3: Add 100 g of 1,2-epoxydecane and 100 g of ethylene oxide-PEG-ethylene oxide (Beijing Bailingwei Technology Co., Ltd., product number: 1685134, molecular weight average MW1,000) into the ball mill, and the mass ratio of the total mass to PUSR is 0.1:1.
[0110] Step 4: Place the ball mill in a ball mill and mill at 400 rpm / min for 12 hours to obtain a dispersion with a particle size of 80 μm.
[0111] Step 5: At room temperature of 25°C, the dispersion obtained in step 4 was placed in a sand mill and sanded using 1.5 mm diameter zirconium oxide balls as sand milling media. The sand milling time was 3 hours, during which 1 ml of triethylamine was added, and the sand milling speed was 3000 rpm. After sand milling, a dispersion with a particle size of 20-100 μm was obtained for the preparation of sponges. The dispersion viscosity data is shown in Table 1. The regenerated soft polyurethane foam is as follows Fig.13 The mechanical properties are shown in Table 2. Compared with Examples 1 and 3, the combination of the two surface modifiers can keep the dispersion viscosity data at 820 mPa·s, which is lower than the dispersion viscosity obtained in Examples 1 and 3, and maintains good viscosity performance. At the same time, the rebound rate of the recycled soft polyurethane foam prepared by the dispersion is 39.2%, the 40% indentation hardness is 144N, and the 75% permanent compression deformation rate is 2.31%, which is not much different from that of Example 2, and meets the requirements of commercial foam mechanical properties.
[0112] Comparative Example 6
[0113] Step 1: The solid PUSR produced after degradation in Preparation Example 1 is mechanically crushed and pulverized at high speed to obtain a powdery solid with a particle size controlled at 10 meshes.
[0114] Step 2: Mix 2kg of powdered PUSR solid with 8kg of composite polyol (allyl alcohol random polyether methyl end-capped purchased from Zhejiang Royal Madrid Technology Co., Ltd. and polyether polyol PPG5623 purchased from Zhejiang Hengfeng New Materials Co., Ltd. in a mass ratio of 3:7). The mixed materials are added to a ball mill. Ball mill beads of different sizes are added to the ball mill, with diameters of 3 mm, 5 mm and 10 mm, respectively, and the number ratio of these beads is 3:2:1.
[0115] Step 3: Add 100 g of propylene oxide and 100 g of ethylene oxide-PEG-ethylene oxide (Beijing Bailingwei Technology Co., Ltd., product number: 1685134, molecular weight average MW1,000) into the ball mill, and the mass ratio of the total mass to PUSR is 0.1:1.
[0116] Step 4: Place the ball mill in a ball mill and mill at 400 rpm / min for 12 hours to obtain a dispersion with a particle size of 80 μm.
[0117] Step 5: At room temperature of 25°C, place the dispersion obtained in step 4 in a sand mill, and use a 1.5mm diameter zirconium oxide ball as a sand milling medium for sand milling. The sand milling time is 3 hours, during which 1ml of triethylamine is added, and the sand milling speed is 3000 rpm. After sand milling, a dispersion with a particle size of 20-100 microns is obtained for the preparation of sponges. The viscosity data of the dispersion are shown in Table 1, and the mechanical properties of the regenerated soft polyurethane foam are shown in Table 2. Compared with Examples 1 and 2, the combination of the two surface modifiers can keep the viscosity data of the dispersion at 960mPa·s, maintaining good viscosity performance. At the same time, the rebound rate, 40% indentation hardness and 75% permanent compression deformation rate of the mechanical properties of the regenerated soft polyurethane foam prepared by the dispersion have little change in values compared with Examples 1 and 2, and still meet the requirements of commercial foam mechanical properties.
[0118] Comparative Example 7
[0119] Step 1: The solid PUSR produced after degradation in Preparation Example 1 is mechanically crushed and pulverized at high speed to obtain a powdery solid with a particle size controlled at 10 meshes.
[0120] Step 2: Mix 2kg of powdered PUSR solid with 8kg of composite polyol (allyl alcohol random polyether methyl end-capped purchased from Zhejiang Royal Madrid Technology Co., Ltd. and polyether polyol PPG5623 purchased from Zhejiang Hengfeng New Materials Co., Ltd. in a mass ratio of 3:7). The mixed materials are added to a ball mill. Ball mill beads of different sizes are added to the ball mill, with diameters of 3 mm, 5 mm and 10 mm, respectively, and the number ratio of these beads is 3:2:1.
[0121] Step 3: Add 100 g of propylene oxide and 100 g of ethylene oxide-PEG-ethylene oxide (Beijing Bailingwei Technology Co., Ltd., product number: 1685134, molecular weight average MW1,000) into the ball mill, and the mass ratio of the total mass to PUSR is 0.1:1.
[0122] Step 4: Place the ball mill in a ball mill and mill at 400 rpm / min for 12 hours to obtain a dispersion with a particle size of 80 μm.
[0123] Step 5: At room temperature of 25°C, the dispersion obtained in step 4 is placed in a sand mill, and a 1.5 mm diameter zirconium oxide ball is used as a sand milling medium for sand milling. The sand milling time is 3 hours, during which 1 ml of triethylamine is added, and the sand milling speed is 3000 rpm. After sand milling, a dispersion with a particle size of 20-100 microns is obtained for the preparation of sponges. The viscosity data of the dispersion are shown in Table 1, and the mechanical properties of the regenerated soft polyurethane foam are shown in Table 2. Compared with Examples 1, 2, and 3, the combination of the three surface modifiers can keep the viscosity data of the dispersion at 750 mPa·s, which is lower than the viscosity of the dispersion obtained in Examples 1, 2, and 3, and maintains good viscosity performance. At the same time, the 75% permanent compression deformation rate in the mechanical properties of the regenerated soft polyurethane foam obtained by the dispersion is significantly smaller than that of Examples 1, 2, and 3, and other indicators do not change much, which meets the requirements of commercial foam mechanical properties.
[0124] Comparative Example 8
[0125] Step 1: The solid PUSR produced after degradation in Preparation Example 2 is mechanically crushed and pulverized at high speed to obtain a powdery solid with a particle size controlled at 10 meshes.
[0126] Step 2: Mix 2kg of powdered PUSR solid with 8kg of composite polyol (allyl alcohol random polyether methyl end-capped purchased from Zhejiang Royal Madrid Technology Co., Ltd. and polyether polyol PPG5623 purchased from Zhejiang Hengfeng New Materials Co., Ltd. in a mass ratio of 3:7). The mixed materials are added to a ball mill. Ball mill beads of different sizes are added to the ball mill, with diameters of 3 mm, 5 mm and 10 mm, respectively, and the number ratio of these beads is 3:2:1.
[0127] Step 3: Place the ball mill in a ball mill and mill at 400 rpm / min for 12 hours to obtain a dispersion with a particle size of 80 microns.
[0128] Step 4: At room temperature of 25°C, place the dispersion obtained in step 4 in a sand mill and use 1.5mm diameter zirconium oxide balls as sand milling media for sand milling. The sand milling time is 3 hours and the sand milling speed is 3000 rpm. After sand milling, a dispersion with a particle size of 20-100 microns is obtained for the preparation of sponge. The viscosity data of the dispersion are shown in Table 1, and the mechanical properties of the regenerated soft polyurethane foam are shown in Table 2. Compared with Example 4, without surface modification treatment, the viscosity of the dispersion is 9180mPa·s, and too high a viscosity value affects the foaming process. The 75% permanent compression set rate in the mechanical properties of the regenerated soft polyurethane foam obtained from the dispersion cannot be measured due to severe deformation of the foam, and does not meet the requirements for the mechanical properties of commercial foams.
[0129] Comparative Example 9
[0130] Step 1: The solid PUSR produced after degradation in Preparation Example 2 is mechanically crushed and pulverized at high speed to obtain a powdery solid with a particle size controlled at 10 meshes.
[0131] Step 2: Mix 2kg of powdered PUSR solid with 8kg of composite polyol (allyl alcohol random polyether methyl end-capped purchased from Zhejiang Royal Madrid Technology Co., Ltd. and polyether polyol PPG5623 purchased from Zhejiang Hengfeng New Materials Co., Ltd. in a mass ratio of 3:7). The mixed materials are added to a ball mill. Ball mill beads of different sizes are added to the ball mill, with diameters of 3 mm, 5 mm and 10 mm, respectively, and the number ratio of these beads is 3:2:1.
[0132] Step 3: Add 200 g of propylene oxide into the ball mill, and the mass ratio of its total mass to PUSR is 0.1:1.
[0133] Step 4: Place the ball mill in a ball mill and mill at 400 rpm / min for 12 hours to obtain a dispersion with a particle size of 80 μm.
[0134] Step 5: At room temperature of 25°C, the dispersion obtained in step 4 was placed in a sand mill and sanded using 1.5 mm diameter zirconium oxide balls as sand milling media. The sand milling time was 3 hours, during which 1 ml of triethylamine was added, and the sand milling speed was 3000 rpm. After sand milling, a dispersion with a particle size of 20-100 μm was obtained for the preparation of sponges. The dispersion viscosity data is shown in Table 1. The regenerated soft polyurethane foam is as follows Fig.14 The mechanical properties are shown in Table 2. Compared with Example 4, through the modification method of the present invention, when the mass ratio of PUSR increases, the viscosity is 1540 mPa·s, which is only slightly higher than that of Example 4, and significantly lower than the viscosity of 7820 mPa·s in Comparative Example 8. At the same time, the mechanical properties of the regenerated soft polyurethane foam prepared from the dispersion are compared with those of Example 4, and the 75% permanent compression deformation rate is slightly increased compared with that of Example 4, but still meets the requirements of the mechanical properties of commercial foams.
[0135] The dispersions prepared in the above-mentioned embodiments and comparative examples were subjected to basic physical property tests, and the results are shown in Table 1. Table 1 is a viscosity table of different samples, and Table 1 is a viscosity data table of the modified embodiments and comparative examples. Too high viscosity will greatly affect the mixing dispersibility and operability of the foaming process. The test results show that with the increase of PUSR solid content, the overall viscosity of the polyurethane foam increases, but through the modification method of the present invention, the viscosity data in all embodiments are lower than that of Comparative Example 1 and Comparative Example 8. Although the addition of PUSR will lead to a slight decrease in foam performance, in comparison, the cost-effectiveness is significant, and the high-value utilization of the solid product of polyurethane foam is achieved.
[0136] Table 1
[0137]
[0138] The polyurethane foams prepared in the above-mentioned embodiments and comparative examples were subjected to mechanical property tests, and the results are shown in Table 2. Table 2 is a comparison of the mechanical properties of different foams. Table 2 is a table of mechanical properties of recycled products prepared in the embodiments and comparative examples. As an indicator that directly reflects the integrity and uniformity of the three-dimensional cross-linked network structure of PUF, the rebound rate is easily affected by the quality of raw materials, thereby affecting the indicators that meet commercial applications. Studies have found that with the increase of the solid content of the solid product, the rebound rate of the foam gradually decreases, and the 40% indentation hardness and 75% permanent compressibility change rate will increase. At the same time, if the solid product is directly dispersed in the polyol, the foamed foam cannot recover after being crushed, and the mechanical properties cannot meet the standards. The introduction of surface modifiers can make the overall foam performance meet commercial indicators.
[0139] Table 2
[0140]
[0141] The above is only a preferred embodiment of the present invention, and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technician familiar with this profession can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the invention. However, any simple modification, equivalent change and modification made to the above embodiments according to the technical essence of the present invention in order to depart from the content of the technical solution of the present invention still falls within the scope of the technical solution of the present invention.
Claims
1. A method for high-value utilization of polyurethane foam degradation solid products, characterized in that: The steps include: Step 1: crushing and grinding the solid product produced after degradation to obtain a powdery solid; Step 2: Mix the powdered solid and the composite polyether polyol in a mass ratio of 20-50:80-50, and add the mixed mixture into a ball mill; Step 3: Adding epoxy surface modifier to the ball mill; Step 4: placing the ball milling jar in a ball mill for ball milling to obtain a dispersion; Step 5: placing the dispersion obtained in step 4 in a sand mill, using sand milling media, adding triethylamine, and sand milling to obtain a dispersion with a particle size of 20-100 microns. The sponge is prepared using the dispersion with a particle size of 20-100 microns.
2. The method for high-value utilization of polyurethane foam degradation solid products according to claim 1, characterized in that: In step 1, the solid product produced after the degradation is obtained by the following method: The polyurethane foam fragments are degraded by an acidolysis method or an alcoholysis method, and the solid product produced after the degradation is obtained after separation.
3. The method for high-value utilization of polyurethane foam degradation solid products according to claim 1, characterized in that: In step 1, the particle size of the powdered solid is controlled at 10-1000 mesh.
4. The method for high-value utilization of polyurethane foam degradation solid products according to claim 1, characterized in that: In step 2, the composite polyether polyol is a mixture of a polyether polyol and a double bond-containing polyol in a mass ratio of 30-50:70-50.
5. The method for high-value utilization of polyurethane foam degradation solid products according to claim 4, characterized in that: In step 2, the double bond-containing polyol is allyl alcohol random polyether methyl terminated or polyether F-6; The polyether polyol is one of polypropylene glycol PPG2000, polyether polyol 5623 and polyether polyol 5602.
6. The method for high-value utilization of polyurethane foam degradation solid products according to claim 1, characterized in that: In step 2, ball milling beads are placed in a ball milling jar.
7. The method for high-value utilization of polyurethane foam degradation solid products according to claim 1, characterized in that: In step three, the epoxy surface modifier is one or more of 1,2-epoxyhexane, ethylene oxide-PEG-ethylene oxide, 1,2-epoxyoctane, 1,2-epoxyheptane, 1,2-epoxydecane, glycidyl phenyl ether, glycidyl methyl ether, 1,2-epoxy-5-hexene, propylene oxide, glycidyl ether, trimethylolpropane triglycidyl ether, and allyl alcohol glycidyl ether.
8. The method for high-value utilization of polyurethane foam degradation solid products according to claim 1, characterized in that: In step three, the mass ratio of the surface modifier to the solid product produced after degradation is 0.01-0.1:
1.
9. The method for high-value utilization of polyurethane foam degradation solid products according to claim 1, characterized in that: In step 4, the ball milling conditions are: ball milling at a speed of 100-800 rpm / min for 8-24 hours.
10. The method for high-value utilization of polyurethane foam degradation solid products according to claim 1, characterized in that: In step 5, the sanding conditions are: the sanding time is 1-3 hours, and the sanding speed is 2000-6000 rpm.
Citation Information
Patent Citations
Method for preparing polyurethane thermal insulation material by recycling waste polyurethane
CN113292700A
Method for preparing polyether polyol by recovering waste rigid polyurethane foam
CN113896880A
Method for recovering polyether polyol from waste rigid polyurethane foam and recovered polyether polyol
CN117004013A
Modified polyol product and method of making modified polyol product
CN117986690A
Recyclate polyol dispersion with improved phase stability
WO2024137494A1
Cited By
Preparation method and application of difunctional modified degradation agent
CN122427207A
